Trajectory of NAFLD characteristics after Roux-en-Y gastric bypass: a five-year historical cohort study - Kreve, Fernanda; Callejas, Guilherme Hoverter; Jimenez, Laísa Simakawa; Marques, Rodolfo Araújo; Chaim, Felipe David Mendonça; Utrini, Murillo Pimentel; Gestic, Martinho Antonio; Ramos, Almino Cardoso; Cazzo, Everton (São Paulo Medical Journal, 2022)
BACKGROUND: The long-term effects of bariatric surgery on the course of non-alcoholic fatty hepatopathy (NAFLD) are not fully understood. OBJECTIVE: To analyze the evolution of NAFLD characteristics through noninvasive markers after Rouxen-Y gastric bypass (RYGB) over a five-year period. DESIGN AND SETTING: Historical cohort study; tertiary-level university hospital. METHODS: The evolution of NAFLD-related characteristics was evaluated among 49 individuals who underwent RYGB, with a five-year follow-up. Steatosis was evaluated through the hepatic steatosis index (HSI), steatohepatitis through the clinical score for non-alcoholic steatohepatitis (C-NASH) and fibrosis through the NAFLD fibrosis score (NFS). RESULTS: 91.8% of the individuals were female. The mean age was 38.3 ± 10 years and average body mass index (BMI), 37.4 ± 2.3 kg/m2. HSI significantly decreased from 47.15 ± 4.27 to 36.03 ± 3.72 at 12 months (P < 0.01), without other significant changes up to 60 months. C-NASH significantly decreased from 0.75 ± 1.25 to 0.29 ± 0.7 at 12 months (P < 0.01), without other significant changes up to 60 months. NFS decreased from 1.14 ± 1.23 to 0.27 ± 0.99 at 12 months (P < 0.01), and then followed a slightly ascending course, with a marked increase by 60 months (0.82 ± 0.89), but still lower than at baseline (P < 0.05). HSI variation strongly correlated with the five-year percentage total weight loss (R = 0.8; P < 0.0001). CONCLUSION: RYGB led to significant improvement of steatosis, steatohepatitis and fibrosis after five years. Fibrosis was the most refractory abnormality, with a slightly ascending trend after two years. Steatosis improvement directly correlated with weight loss.